A - Solomon, Robert C. (Oxford University Press, 1999)
Is business ethics a contradiction in terms? Absolutely not, says Robert Solomon. In fact, he maintains that sound ethics is a necessary precondition of any long-term business enterprise, and that excellence in business must exist on the foundation of values that most of us hold dear